Pharmacy installation performance analysis of Blitar Hospital through a balanced scorecard approach with a SWOT analysis framework in 2023 - Wahyuningtiyas, Triya; Purwidyaningrum, Ika; Wijayanti, Tri (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2024)
Background: The development of Blitar Hospital results from collaborative deliberation that requires comprehensive planning, financial allocation, intellectual consideration, and a strategic approach to achieve optimal results. Method: This study aims to evaluate the performance of the Pharmacy Installation using the Balanced Scorecard approach with SWOT to determine the position of the Pharmacy Installation as a strategy preparation. This type of research is descriptive non-experimental. Data were obtained through in-depth interviews with the Head of the Pharmacy Installation, questionnaires to employees and patients, and direct observation. Qualitative and quantitative descriptive analysis was used. Results: The results showed that performance: 1) Financial perspective: ITOR 2022 (6 times), 2023 (7.7 times); GPM 2022 (26.50%), 2023 (30.61%); GROSS 2022 (61%), 2023 (23.82%). 2) Internal business process perspective: Drug availability rate 2022 (98.48%), 2023 (97.96%); dispensing time of concocted prescription (47.30 minutes), non-concocted prescription (31.54 minutes); Provision of drug information: delivered 100%, except side effects (2.63%), duration of use (4.28%), Storage method (0%). 3) Growth and learning perspective: Employee morale is high; SIM needs feature optimization; Employee training level (100%). 4) Customer perspective: Patients are satisfied with the pharmacy installation services; customer retention period I (52%), period II 2023 (37%); customer acquisition period I (48%), period II (65%). SWOT analysis shows that the Pharmacy Installation is in quadrant II with a diversification strategy. Conclusion: The performance of Pharmacy Installation Blitar Hospital is good and can be improved.